Chemical constituents and biological activities of endophytic fungi from Fagopyrum dibotrys - Qiqi Xie; Yujie Jia; Jiwen Tao; Tongliang Bu; Qing Wang; Nayu Shen; Xinyu Zhang; Yirong Xiao; Lin Ye; Zhao Chen; Huahai Huang; Qingfeng Li; et al. (PeerJ)
Background Fagopyrum dibotrys is an important wild food and feed germplasm resource. It has high nutritional and medicinal value and is rich in natural products, including flavonoids, phenolic acids, coumarins, and alkaloids. Endophytic fungi in F. dibotrys have emerged as valuable sources of natural products. However, studies on the biological activity and chemical composition of these endophytic fungi remain limited. Methods In this paper, a new method to obtain natural active ingredients by fermentation of endophytic fungi from medicinal plants was proposed. Then the antioxidant and pathogenic activities of the endophytic fungi extracts were determined in vitro. In addition, secondary metabolites produced by endophytic fungi with medicinal activity were analyzed by high performance liquid chromatography-tandem mass spectrometry (LC-MS). Results Among the 95 endophytic fungal strains in F. dibotrys, four strains with high phenol yields were selected by reaction: Alternaria alstroemeriae (J2), Fusarium oxysporum (J15), Colletotrichum karsti (J74), and Colletotrichum boninense (J61). Compared with those of various extracts, the ethyl acetate fractions of A. alstroemeriae (J2), F. oxysporum (J15), and C. boninense (J61) exhibited superior antioxidant and antibacterial properties. The results indicated that the fungal extract was an excellent natural antioxidant and might be a potential antibacterial agent. The DPPH free radical clearance of A. alstroemeriae was 94.96 ± 0.004%. These findings indicated that A. alstroemeriae had strong antioxidant activity. In addition, the extract of A. alstroemeriae had good antibacterial activity against Escherichia coli and Staphylococcus aureus, with MICs of 0.5 and 0.05 mg/mL, respectively. The chemical constituents of the ethyl acetate extract from A. alstroemeriae were further analyzed by liquid chromatography–mass spectrometry (LC–MS). We noted that A. alstroemeriae can create a variety of medicinal substances that have high value in medicine, such as caffeic acid (884.75 ng/mL), 3-phenyllactic acid (240.72 ng/mL) and norlichexanthone (74.36 ng/mL). Discussion In summary, many valuable active substances and medicinal substances can be obtained through the study of endophytic fungi of F. dibotrys.